A checklist of the Robber Flies (Insecta: Diptera: Asilidae) of Wyoming, USA - Lavigne, Robert J.; Dennis, D. Steve (Zootaxa, 2017)
A checklist of 158 species of Wyoming robber flies (Insecta: Diptera: Asilidae) is presented for the first time based on personal collecting, literature review, museum specimens, and online databases. In Wyoming, asilid habitats range from arid desert environments to mountainous pine-douglas fir forests. According to the latest classification system of Dikow (2009), these include 54 species of Asilinae, 24 species of Brachyrhopalinae, 10 species of Dasypogoninae, 3 species of Dioctriinae, 23 species of Laphriinae, 8 species of Leptogastrinae, 24 species of Stenopogoninae, 8 species of Stichopogoninae, 1 species of Trigonomiminae, and 3 species of Willistonininae. Thirty-one of these species have not been previously recorded as occurring in Wyoming.